2012
DOI: 10.1371/journal.pone.0046156
|View full text |Cite
|
Sign up to set email alerts
|

Combining Epidemiological and Genetic Networks Signifies the Importance of Early Treatment in HIV-1 Transmission

Abstract: Inferring disease transmission networks is important in epidemiology in order to understand and prevent the spread of infectious diseases. Reconstruction of the infection transmission networks requires insight into viral genome data as well as social interactions. For the HIV-1 epidemic, current research either uses genetic information of patients' virus to infer the past infection events or uses statistics of sexual interactions to model the network structure of viral spreading. Methods for a reliable reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Unlike the latter, they found only a modest direct effect of network configuration on phylogenies. Another study presents an attempt to directly reconstruct a sexual contact network, underlying HIV transmission, based on epidemiological and genetic information [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the latter, they found only a modest direct effect of network configuration on phylogenies. Another study presents an attempt to directly reconstruct a sexual contact network, underlying HIV transmission, based on epidemiological and genetic information [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies discussed approaches for integration of genetic and social network data [35, 36, 38, 89, 119]. In the absence of known exposures between cases, or in the case of ineffective contact investigations, molecular epidemiology or genomic approaches can identify potential members of an outbreak cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that simulations were successful in predicting the outbreak spread when compared with real life data. In 2012, Zarrabi et al [40] proposed a filter-reduction method to study the HIV infection using social interactions and genetic information. In 2014, Duan et al [41] studied the spreading velocity of any epidemic based on topology of weighted graph created.…”
Section: Ict and Mathematical Models In H1n1 Epidemicmentioning
confidence: 99%